Keefektifan Sosiodrama untuk Meningkatkan Komunikasi Interpersonal Siswa SMA - Miftahul Jannah; Abdullah Pandang; Fitriana Fitriana (Universitas Sebelas Maret, 2026)
Poor interpersonal communication skills are frequently observed in school settings, where some students struggle to interact with both teachers and peers. This study examines the effect of sociodrama techniques on students' interpersonal communication, with particular attention to openness and equality. A quantitative, nonequivalent control group experimental design was used in this research. The participants in the research were 10 students in the experimental group and 10 students in the control group, who identified as having low interpersonal communication skills. Data collection involved an interpersonal communication questionnaire, with analysis conducted using Mann-Whitney tests. The results demonstrate that Sociodrama techniques significantly improved students' interpersonal communication skills, as evidenced by Mann-Whitney tests with p-value 0.001 (0.001<0.05). The sociodrama technique was implemented through the stages of script determination, role comprehension, role enactment, and evaluation of role play outcomes. These findings suggest that sociodrama techniques are effective in enhancing high school students' interpersonal communication skills.